Identification of the Pyroptosis-Related Gene Signature for Overall Survival Prediction in Patients With Hepatocellular Carcinoma - Liu, Shuang; Shao, Ruonan; Bu, Xiaoyun; Xu, Yujie; Shi, Ming (Frontiers in Cell and Developmental Biology, 2021)
Hepatocellular carcinoma (HCC) is the second most lethal malignant tumor worldwide, with an increasing incidence and mortality. Due to generally resistance to antitumor drugs, only limited therapies are currently available for advanced HCC patients, leading to a poor prognosis with 5-year survival rate less than 20%. Pyroptosis is a type of inflammation-related programmed cell death and may become a new potential target for cancer therapy. However, the function and prognostic value of pyroptosis-related genes (PRGs) in HCC remains unknown. Here, we identified a total of 58 PRGs reported before and conducted a 6-PRGs signature via LASSO regression method in GEO training cohort and model efficacy was further validated in external dataset. The HCC patients can be classified into two subgroups based on median risk score. High-risk patients have significantly shorter overall survival (OS) than low-risk patients both in training and validation cohort. Multivariable analysis indicated that the risk score was an independent prognostic factor for OS of HCC patients. Functional enrichment analysis and immune infiltration evaluation suggested that immune status was more activated in low-risk group. In summary, PRGs can be a prediction factor for prognosis of HCC patients and targeting pyroptosis is a potential therapeutic alternative in HCC.